2009
DOI: 10.1002/cncr.24152
|View full text |Cite
|
Sign up to set email alerts
|

CA‐125 change after chemotherapy in prediction of treatment outcome among advanced mucinous and clear cell epithelial ovarian cancers

Abstract: Background-There are limited data regarding unique clinical or laboratory features associated with advanced clear cell (CC) and mucinous (MU) epithelial ovarian cancers (EOC), particularly the relationship between CA-125 antigen levels and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 29 publications
2
54
2
Order By: Relevance
“…For example in the Gynecologic Oncology Group, ovarian cancer investigators have implemented clinical trials based on histological cell types including clear cell, mucinous, and sex cord stromal tumors. [10][11][12] In large population-based studies, our research group demonstrated that ovarian serous cancers have better prognosis compared with clear cell cancers. Moreover, Hemminki et al 6 showed adenocarcinomas have worse outcomes as compared with squamous cell carcinomas in cancers of unknown origin.…”
Section: Commentmentioning
confidence: 99%
“…For example in the Gynecologic Oncology Group, ovarian cancer investigators have implemented clinical trials based on histological cell types including clear cell, mucinous, and sex cord stromal tumors. [10][11][12] In large population-based studies, our research group demonstrated that ovarian serous cancers have better prognosis compared with clear cell cancers. Moreover, Hemminki et al 6 showed adenocarcinomas have worse outcomes as compared with squamous cell carcinomas in cancers of unknown origin.…”
Section: Commentmentioning
confidence: 99%
“…CA125 was originally identified following the development of the OC125 antibody and was found to be elevated in about 80% of patients with cancer of ovary and in 30% of patients with any primary cancer with extensive intraabdominal disease [8]. Therefore, even if CA125 generally has a high sensitivity, its clinical use in confirming OC is limited because it is also frequently increased in women with benign gynecological diseases as well as benign diseases associated with inflammatory cells of the pleura, pericardium, and peritoneum [9][10][11]. For these reasons, numerous studies have been conducted in order to identify a marker with high specificity and sensitivity for OC diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…20 Seven exploratory analyses and 1 translational-research project have involved GOG 158 patients. [26][27][28][29][30][31][32][33] Although details of each GOG 158 ancillary project are beyond the scope of this article, 2 are mentioned in this chapter. GOG 158 was 1 of 2 trials that addressed the implications of a second-look laparotomy after optimally debulked ovarian carcinoma and is discussed in further detail in a section below.…”
Section: Gog Protocols and Ovarian Cancer 137mentioning
confidence: 99%